Genitourinary syndrome of menopause: hard to communicate, easy to treat - Fait, Tomáš (Casopis lekaru ceskych, 2019)
About 40 % of woman suffer from vulvovaginal atrophy after menopausal transition. It is very important to put question on this problem, because about 70 % of them are not able to start discussion on it. Regarding treatment, vaginal low doses estriol and estradiol are drugs of first choice with high efficacy and safety.
Keywords: menopauza; vagina; Menopause; estriol; prasteron; vulvovaginal atrophy; lidé; ospemifene; genitourinary syndrome of menopause; atrofie; vaginal application; ženské pohlaví; Humans; nemoci vulvy; syndrom; Vaginal Diseases; Female; Vulvar Diseases; estradiol; Syndrome; vaginální onemocnění; Vagina; Atrophy